Effects of Task and Personality Characteristics on Subordinate Responses to Participative Decision Making - Abdel‐Halim, Ahmed A. (Academy of Management Journal, 1983)
The effects of task and personality characteristics on subordinate responses to participatory decision making were investigated among 229 supervisor-subordinate pairs. Contrary to prediction, high need-for-independence subordinates performed better and were more satisfied with high participation only for nonrepetitive tasks.